Assessment of GeneXpert MTB/RIF performance for tuberculosis at doctor chasbullah abdulmajid hospital, bekasi city - Hawafirdaus, Denty; B Shurianto, Lily; Ratunanda, Susanti (ACTA Medical Health Sciences, 2025)
Tuberculosis (TB) remains a critical global health threat, with effective detection methods continuing to pose challenges. Since 2012, the Indonesian National TB Control Program has utilized the GeneXpert examination with the Xpert MTB/RIF (Mycobacterium Tuberculosis/Rifampicin) cartridge, enabling rapid identification of Mycobacterium tuberculosis (MTB) and simultaneous detection of rifampicin resistance. This descriptive study assesses the performance of the GeneXpert MTB/RIF assay in patients at Doctor Chasbullah Abdulmajid Hospital. Results were classified into successful tests (MTB detected, MTB not detected, MTB detected with rifampicin resistance, and MTB detected with rifampicin indeterminate) and failed tests (invalid, error, and no result). Data were sourced from the National Tuberculosis Information System (SITB), comprising 2,408 patients who met the inclusion criteria. The findings indicate that most suspected TB patients were between 19 and 44 years old (36.62%), with a higher prevalence in males (58.39%) than in females (41.6%). The majority were new TB cases (88.88%). The GeneXpert MTB/RIF assay exhibited an impressive 99.8% success rate, alongside a failure rate of 0.12%. Among successful tests,30.06% detected MTB, with 26.61% being rifampicin-sensitive and 3.44% resistant. Notably, 69.80% of tests resulted in undetectable MTB. Error results may arise from various factors, including undetectable MTB DNA and system malfunctions. While a significant number of negative results were observed, these findings merit further investigation, particularly in suspected pediatric TB cases. DOI : 10.35990/amhs.v3n3.p141-150 REFERENCES Indonesia Ministry of Health. Health Community Movement. Tuberculosis Examination GeneXpert Molecular Rapid Test Instructions Manual. 2023. Indonesia Ministry of Health. Report on Tuberculosis Control Program in 2022. 2023. World Health Organization. WHO Operational Handbook on Tuberculosis: Module 3 – Rapid diagnostics for Tuberculosis Detection. 3rd ed. 2024. World Health Organization. Global Tuberculosis Report 2023. Geneva: WHO; 2023. Indonesia Ministry of Health. 2023 Tuberculosis Program Monitoring and Evaluation Meeting. 2023. Sahiratmadja E, Mega GS, Andriyoko B, Parwati I. Performance of Xpert® MTB/RIF in detecting multidrug-resistant tuberculosis in West Java, Indonesia. Majalah Kedokteran Bandung. 2020;52(2):99–106. Newtonraj A, Venables E, Selvaraj K, Kundu D, Purty A, Manikandan M, et al. Xpert negative means no TB: A mixed-methods study into early implementation of Xpert in Puducherry, India. J Family Med Prim Care. 2019;8(4):1379. Kohli M, Schiller I, Dendukuri N, Yao M, Dheda K, Denkinger CM, et al. Xpert MTB/RIF Ultra and Xpert MTB/RIF assays for extrapulmonary tuberculosis and rifampicin resistance in adults. Cochrane Database Syst Rev. 2021;2021(1). Gidado M, Nwokoye N, Ogbudebe C, Nsa B, Nwadike P, Ajiboye P, et al. Assessment of GeneXpert MTB/RIF performance by type and level of healthcare facilities in Nigeria. Niger Med J. 2019;60(1):33. Rolo M, González-Blanco B, Reyes CA, Rosillo N, López-Roa P. Epidemiology and factors associated with extrapulmonary tuberculosis in a low-prevalence area. J Clin Tuberc Other Mycobact Dis. 2023;32:100377. Rivani E, Sabrina T, Patricia V. Comparison of GeneXpert MTB/RIF diagnostic test to detect rifampicin resistance of Mycobacterium tuberculosis in pulmonary TB patients at RSUP Dr. Moh. Hoesin Palembang. JKK. 2019;6(1). Lamberto M, Mboeik W, Wicaksono Pitoyo C, Karjadi TH, Karuniawati A, Dewiasty E. Performance of Xpert MTB/RIF using gastric lavage samples in diagnosing pulmonary tuberculosis in HIV patients suspected of pulmonary tuberculosis. J Penyakit Dalam Indonesia. 2018;5. Dewi AIS, Andrika P, Artana IB, Kunci K. Characteristics of tuberculosis patients in the Respiratory Department of Sanglah Hospital, Denpasar. Available from: https://ojs.unud.ac.id/index.php/eum Kesek J, Cerelia S, Polii E. Characteristics and demographics of pulmonary tuberculosis patients of productive age at Prof. Dr. R. D. Kandou General Hospital Manado for the period 2014–2015. 2019 [cited 2024 Sep 10]; Available from: https://ejournal.unsrat.ac.id/index.php/msj Caraux-Paz P, Diamantis S, de Wazières B, Gallien S. Tuberculosis in the elderly. J Clin Med. 2021;10(24):5888. Putri PA, Setyoningrum RA, Handayani S, Rosyid AN. Correlation between demographic factors and tuberculosis prevention: A literature review. Int J Res Publ. 2022;115(1). Indonesia Ministry of Health. Changes in Diagnosis and Treatment of Tuberculosis Protocols in Indonesia. 2021 Apr. Rarome BB, Aisah N, Setyoningrum RA, Mertaniasih NM. GeneXpert MTB/RIF and Mycobacterium tuberculosis sputum culture in establishing the diagnosis of pulmonary tuberculosis and rifampicin resistance in suspected childhood pulmonary tuberculosis in Soetomo Hospital. Int J Tuberc Infect Dis. [Internet]. Available from: https://e-journal.unair.ac.id/IJTID/ Arbués MD, Rossetti MLR. Evaluation of the GeneXpert MTB/RIF to diagnose tuberculosis in a public health laboratory. Rev Saude Publica. 2024;58(1):3. Huang W, Lee MKT, Sin ATK, Nazari RS, Chua SY, Sng LH. Evaluation of Xpert MTB/RIF Ultra assay for detection of Mycobacterium tuberculosis and rifampicin resistance. Pathology. 2023;55(5):688–97. Alemu A, Amare M, Ameni G, Kebede A, Beyene D, Yenew B, et al. Monitoring quality indicators for the Xpert MTB/RIF molecular assay in Ethiopia. PLoS One. 2019;14(11).